GARREC: ferramenta de apoio no processo de certificação de software da CERTICS - Medeiros, Adriana Gonçalves Silva de (2017)
The CERTICS certification was developed to be a public policy tool that seeks to contribute to sustainable national development and it can support national software companies in the evolution required to become more competitive compared to the foreign software. However, this certification, as well as others, requires professional investment and financial resources, which is usually a problem for small software companies. This work aims to present GARREC, Guide for Meeting the Requirements of Results Expected from CERTICS, which is a tool developed to support the understanding and obtaining of the CERTICS certification, working in addition to the existing documentation. GARREC was built to facilitate the understanding of the CERTICS’ concepts and in meeting the expected results through evidence proposition considering small business scenarios.Therefore, GARREC will contribute to reducing the investment required for certification. The research method involved the analysis of the Reference Model for Evaluation of CERTICS and detailing of the Specific Requirements of its Expected Results, and for these, evidence was presented to meet them, classified by relevance. In this way all evaluated aspects are considered, guaranteeing quality of coverage of the attendance to the certification requirements. For the GARREC evaluation, an experiment was carried out in which the participants used it to meet predetermined expected results and answered to a survey. Three companies with different levels of knowledge of CERTICS, a certified company, one in the process of certification and one without previous knowledge participated in the experiment. Based on the results of the evaluation survey, GARREC achieves its objectives of assisting in the understanding and fulfillment of CERTICS certification requirements, with 91.3% acceptance of the items referring to Effectiveness and, 97.5% acceptance of the related items Applicability. Further validation in the field is still necessary for a more consistent evaluation of the tool.